Severe metabolic changes following oral sodium phosphate in a patient of renal cell carcinoma-on dialysis - Lim, Christopher Thiam Seong (Medknow Publications and Media, 2016)
Oral sodium phosphate (OSP), an effective bowel purgative, is available over the counter (OTC) and requires a substantially lower volume than polyethylene glycol-based preparative agents. Rarely, OSP consumption has been associated with acute hypocalcemia and hyperphosphatemia. We describe a case of chronic kidney disease patient developing symptomatic hypocalcemia following OTC OSP.